Future Path Toward TB Vaccine Development: Boosting BCG or Re-educating by a New Subunit Vaccine - Gupta, Nancy; Garg, Saurabh; Vedi, Satish; Kunimoto, Dennis Y.; Kumar, Rakesh; Agrawal, Babita (Frontiers in Immunology, 2018)
Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis (Mtb), kills 5000 people per day globally. Rapid development and spread of various multi drug-resistant strains of Mtb emphasize that an effective vaccine is still the most cost-effective and efficient way of controlling and eradicating TB. Bacillus Calmette-Guerin (BCG), the only licensed TB vaccine, still remains the most widely administered human vaccine, but is inefficient in protecting from pulmonary TB in adults. The protective immunity afforded by BCG is thought to wane with time and considered to last only through adolescent years. Heterologous boosting of BCG-primed immune responses using a subunit vaccine represents a promising vaccination approach to promote strong cellular responses against Mtb. In our earlier studies, we discovered lipopeptides of ESAT-6 antigen with strong potential as a subunit vaccine candidate. Here, we have investigated that potential as a booster to BCG vaccine in both a pre-exposure preventive vaccine and a post-exposure therapeutic vaccine setting. Surprisingly, our results demonstrated that boosting BCG with subunit vaccine shortly before Mtb challenge did not improve the BCG-primed immunity, whereas the subunit vaccine boost after Mtb challenge markedly improved the quantity and quality of effector T cell responses and significantly reduced Mtb load in lungs, liver and spleen in mice. These studies suggest that ESAT-6 lipopeptide-based subunit vaccine was ineffective in overcoming the apparent immunomodulation induced by BCG vaccine in Mtb uninfected mice, but upon infection, the subunit vaccine is effective in re-educating the protective immunity against Mtb infection. These important results have significant implications in the design and investigation of effective vaccine strategies and immunotherapeutic approaches for individuals who have been pre-immunized with BCG vaccine but still get infected with Mtb.